2017
DOI: 10.21859/jech-02048
|View full text |Cite
|
Sign up to set email alerts
|

Student-Life Stress Level and its Related Factors among Medical Students of Hamadan University of Medical Sciences in 2015

Abstract: background and Objectives: Student-life stress can lead to various negative consequences such as physical illness, mental disorders or exhaustion. The present study was conducted to evaluate the level of student life stress and its related factors among medical students of Hamadan University of Medical Sciences. Materials and Methods: This cross-sectional study applied multistage random sampling to select 500 university students at Hamadan University of Medical Sciences during 2015. The data collection tool us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
1
3
0
1
Order By: Relevance
“…can impose severe stress on undergraduate students. The results of the present study were consistent with Nikanjam study [19].…”
Section: Demographic Characteristics and Its Relationship With The Co...supporting
confidence: 93%
“…can impose severe stress on undergraduate students. The results of the present study were consistent with Nikanjam study [19].…”
Section: Demographic Characteristics and Its Relationship With The Co...supporting
confidence: 93%
“…Researchers indicated that there is a significant relationship between age and academic stress of students (Nikanjam et al, 2017). There was a significant difference between depression and anxiety in terms of age variable, such that rate of disorders was increased with age (Sadeghian et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Kakabraei et al (2013) found a negative and significant relationship between objective pressures and academic stress with academic satisfaction. In a recent study, Nikanjam et al (2022) showed that academic stress and academic performance have a negative and significant relationship. In other words, these two variables had negative correlations as the increase of academic stress decreased learners' academic performance.…”
Section: Empirical Studiesmentioning
confidence: 99%